Adsorption of Sinapine from Rapeseed Protein Production Effluent to Cation Exchange Resins - Fatima Zahra Kdah; Arnaud Aymes; Luna Beau; Armelle Ropars; Jean-Pol Frippiat; Romain Kapel (Separations)
Sinapine adsorption was studied on four weak cation exchanges at pHs ranging from 2 to 8. The best adsorption rate was observed with C106 resin at pH 4 (95.25%). The adsorption kinetics followed a pseudo-second-order model while the isotherm data better fitted the Langmuir model. The ΔG°, ΔH°, and ΔS° values (−25.834 kJ·mol−1, −24.428 kJ·mol−1, and 0.004 kJ·mol−1·K−1) revealed that the adsorption process was spontaneous and exothermic. Acidified ethanol showed a better desorption rate (75.41%), while virtually no (3.32%) or low (31.14%) sinapine desorption was observed with 50% ethanol and 0.1 M HCl solution, respectively. This indicated that sinapine adsorption took place throughout both ionic and hydrophobic interactions. Very close sinapine adsorption performances were observed with an effluent of the patented rapeseed protein isolate process. Two-step desorption using 50% ethanol, then acidified ethanol, yielded a highly purified neutral sinapine-derivative phenol fraction (75.23%) in the first elution fraction and sinapine (98.85%) in the second one.